PENGARUH KUALITAS BAHAN BAKU DAN RASIO UMPAN TERHADAP PELARUT PADA PROSES PEMURNIAN GARAM DENGAN METODE HIDROEKSTRAKSI BATCH - Angela Martina, Judy Retti Witono, Ginajar Karya Pamungkas, Willy (Universitas Sumatera Utara, 2016)
Nowadays, Indonesia is still relying on the imported salt, especially from Australia to meet the domestic salt demand. Development of salt purification process is still ventured to improve the quality of the salt as well as the efficiency. In this research, salt purification process is done using the hydroextraction method, where the salt crystals are purified using the pure saturated salt solution in a beaker glass. Different classification of salt K1, K2, and K3 are used with F:S ratio is varied by 1:30; 1:35; 1:40; 1:45; and 1:50. The hydroectraction process is stirred at 50 rpm. The quality of the purified salt are determined based on analysis of the levels of NaCl, Ca2+, and Mg2+. The highest NaCl level, 98,89% obtained on the process using K2 salt with F:S ratio is 1:45.